Generating statistics from health facility data: the state of routine health information systems in Eastern and Southern Africa. Issue 5 (September 2019) - Maïga, Abdoulaye; Jiwani, Safia S; Mutua, Martin Kavao; Porth, Tyler Andrew; Taylor, Chelsea Maria; Asiki, Gershim; Melesse, Dessalegn Y; Day, Candy; Strong, Kathleen L; Faye, Cheikh Mbacké; Viswanathan, Kavitha; O'Neill, Kathryn Patricia; et al.
Abstract : Health facility data are a critical source of local and continuous health statistics. Countries have introduced web-based information systems that facilitate data management, analysis, use and visualisation of health facility data. Working with teams of Ministry of Health and country public health institutions analysts from 14 countries in Eastern and Southern Africa, we explored data quality using national-level and subnational-level (mostly district) data for the period 2013–2017. The focus was on endline analysis where reported health facility and other data are compiled, assessed and adjusted for data quality, primarily to inform planning and assessments of progress and performance. The analyses showed that although completeness of reporting was generally high, there were persistent data quality issues that were common across the 14 countries, especially at the subnational level. These included the presence of extreme outliers, lack of consistency of the reported data over time and between indicators (such as vaccination and antenatal care), and challenges related to projected target populations, which are used as denominators in the computation of coverage statistics. Continuous efforts to improve recording and reporting of events by health facilities, systematic examination and reporting of data quality issues, feedback and communication mechanisms between programme managers, care providers and data officers, and transparent corrections and adjustments will be critical to improve the quality of health statistics generated from health facility data.